UPAYA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH (BPPRD) DALAM MENINGKATKAN PENERIMAAN PAJAK RESTORAN DI KABUPATEN KUBU RAYA - Tiara Aprili; Novi Desanti; Desvira Zain; Ade M. Yuardani (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2019)
The title of this research was “The Effort of Regional Tax and Retribution Management Agency (BPPRD) of Kubu Raya Regency in Increasing Tax Restaurant Reception”. Therefore, this study focuses on the Efforts of BPPRD Kubu Raya in Increasing Tax Restaurant. The purposes of this research were to know the effort of BPPRD of Kubu Raya Regency in increasing the revenue of tax restaurant, the obstacles of increasing the acceptance of tax restaurant, and the solution in overcoming the obstacle that happened. This research used qualitative research with descriptive method. The result of data analysis showed that in increasing the revenue of tax restaurant through tax intensification did an improvement. Tax that related to the laws, administrative simplifications, reordering the number of subject/tax object restaurants and improving the quality of Human Resources. While extensification of restaurant taxes such as increasing the number of subject/objects of existing taxes, make improvements in tariffs, and conduct supervision of taxpayers. The other obstacles in increasing the tax restaurant was the existence of passive and active resistance from the community, the limitations of Human Resources, and many areas that have not been explored optimally due to the distance between sub districts. Furthermore, the solution to overcome the obstacles were did socialization to the community continuously, open up the opportunities for businessman, making Human Resources effective and implemented the bonbill system. Keywoard : Effort, Restaurant Tax, BPPRD